Gregory of Tours : life of the Fathers - Gregorius Turonensis, 539-594 (Translated texts for historians ;, 1991)
The first translation into English of Life of the Fathers, a collection of twenty lives of saints which lives present a cross-section of the Gallic Church and are a counterpart to the secular society described in Gregory’s History of the Franks.